152k views
3 votes
The graph of f(x) = x2 has been shifted into the form f(x) = (x − h)2 + k:

The graph of f(x) = x2 has been shifted into the form f(x) = (x − h)2 + k:-example-1
User Emad Adly
by
5.3k points

2 Answers

5 votes

Answer:

3

Explanation:

H is a horizontal shift to the right. The graph went over 2, so h=2. From there the graph went up 3 (vertical shift) so K=3

User FotNelton
by
5.5k points
5 votes
The answer is 3 because it is shifted up 3 spots
User Sterling Nichols
by
5.6k points